Size/morphology induced tunable luminescence in upconversion crystals: ultra-strong single-band emission and underlying mechanisms1. Issue 21 (7th June 2015) - Wang, Zhaofeng; Zeng, Songshan; Yu, Jingfang; Ji, Xiaoming; Zeng, Huidan; Xin, Shuangyu; Wang, Yuhua; Sun, Luyi
<x xml:space="preserve">Abstract</x> The size/morphology dependent upconversion of Lu5O4F7:Er3+, Yb3+ was investigated, and an ultra-strong single-band upconversion was obtained in the nanoparticles.